Extreme Value Analysis of Ground Magnetometer Observations at Valentia Observatory, Ireland - Alexandra Ruth Fogg; C. M. Jackman; J. Malone‐Leigh; P. T. Gallagher; A. W. Smith; M. Lester; M.‐T. Walach; J. E. Waters (Space Weather)
Abstract Understanding global space weather effects is of great importance to the international scientific community, but more localized space weather predictions are important on a national level. In this study, data from a ground magnetometer at Valentia Observatory is used to characterize space weather effects on the island of Ireland. The horizontal component of magnetometer observations and its time derivative are considered, and extreme values of these are identified. These extremes are fit to a generalized extreme value distribution, and from this model return values (the expected magnitude of an observation within a given time window) are predicted. The causes of extreme values are investigated both in a case study, and also statistically by looking at contributions from geomagnetic storms, substorms, and sudden commencements. This work characterizes the extreme part of the distribution of space weather effects on Ireland (and at similar latitudes), and hence examines those space weather observations which are likely to have the greatest impact on susceptible technologies.